Rebels and Runaways : Slave Resistance in Nineteenth-Century Florida - Rivers, Larry E., 1950- (Book collections on Project MUSE., 2012)
This study examines slave resistance and protest in antebellum Florida and its local and national impact from 1821 to 1865. The author discusses Florida's historical significance as a runaway slave haven dating back to the 17th century.